2013
DOI: 10.1242/jeb.088914
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of mammalian maximal oxygen consumption during exercise

Abstract: SUMMARY We compiled published values of mammalian maximum oxygen consumption during exercise (V ·O2Supplementary material available online at http://jeb.biologists.org/lookup/suppl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 116 publications
5
55
0
1
Order By: Relevance
“…The idea behind the development of the needed additional relations is that the variables associated directly with the "characteristic" capillary system described above can be expected to apply also to the capillaries of the ventricles, since their mass is proportional to body mass. Thus, the number of capillaries in the ventricles can be considered proportional to the number of capillaries n c associated with the Equations (7) and (8). The number of related cardiac cells in the ventricles can also be considered to be proportional to the number of capillaries supplying them.…”
Section: The Cardiovascular Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The idea behind the development of the needed additional relations is that the variables associated directly with the "characteristic" capillary system described above can be expected to apply also to the capillaries of the ventricles, since their mass is proportional to body mass. Thus, the number of capillaries in the ventricles can be considered proportional to the number of capillaries n c associated with the Equations (7) and (8). The number of related cardiac cells in the ventricles can also be considered to be proportional to the number of capillaries supplying them.…”
Section: The Cardiovascular Systemmentioning
confidence: 99%
“…This could be the case if physiological variables such as oxygen consumption rate and heart rate increased by the same factor for all mammals. This is now known not to be the case as a result of work by Baudinette [35], Taylor and Weibel [36], Weibel and Hoppeler [37], Bishop [38,39] and, most recently, Dlugosz et al [8], among others.…”
Section: Effects Of Strenuous Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…The use of treadmills, enclosed running wheels, air tunnels and water flues as well as open flow respirometry systems has resulted in a large number of MMR values for different-sized animals. The most recent analysis of MMR and body size of mammals [41] has shown that there is no significant difference between values obtained using treadmills or running wheels and found 0.84 to be the scaling exponent. The 95% confidence intervals (0.80-0.88) include values reported for mammals by two earlier studies; 0.81 by [42] and 0.87 by [43].…”
Section: Metabolic Rate and Body Size: Metabolic Rates Other Than Bmrmentioning
confidence: 99%
“…The essential act of blood is to maintaining of hemostasis of internal tissues of body. A lot of actions are done in the body which changes the internal environment of chemical component, for example some changes will occur by contraction of muscles [5]. A cell that contains hemoglobin and can carry oxygen to the body.…”
Section: Introductionmentioning
confidence: 99%